2014
DOI: 10.3892/mco.2014.436
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative mean platelet volume in resected non-small-cell lung cancer

Abstract: Abstract. An increased mean platelet volume (MPV) is an early marker of platelet activation. MPV was also shown to be associated with the pathophysiological characteristics of various types of cancer. A previous study demonstrated that MPV was significantly associated with the overall survival (OS) of patients with advanced non-small-cell lung cancer (NSCLC). However, there has been no analysis of the prognostic effect of MPV on patients with resected NSCLC. The aim of this study was to evaluate the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 19 publications
3
72
2
2
Order By: Relevance
“…There are many studies demonstrated that increased MPV was significantly related with colon cancer (Li et al, 2014), lung cancer (Kumagai et al, 2015), gastric cancer (Kılınçalp et al, 2014), endometrial carcinoma (Karateke et al, 2015) and in head and neck neoplasms (Eryilmaz et al, 2015). In the literature, increased N/L ratio was significantly related with the lung cancer (Kemal et al, 2014), gastric cancer (Kim et al, 2015), colon cancer (Absenger et al, 2013) and papillary thyroid cancer DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4.2321 Inflammatory Hematological Parameters in Benign Nodular Goiter andPapillary Thyroid Cancer (Seretis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies demonstrated that increased MPV was significantly related with colon cancer (Li et al, 2014), lung cancer (Kumagai et al, 2015), gastric cancer (Kılınçalp et al, 2014), endometrial carcinoma (Karateke et al, 2015) and in head and neck neoplasms (Eryilmaz et al, 2015). In the literature, increased N/L ratio was significantly related with the lung cancer (Kemal et al, 2014), gastric cancer (Kim et al, 2015), colon cancer (Absenger et al, 2013) and papillary thyroid cancer DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4.2321 Inflammatory Hematological Parameters in Benign Nodular Goiter andPapillary Thyroid Cancer (Seretis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a considerable decrease in the MPV values in some types of cancer (Oncel et al, 2015). Others reported that a significant decrease in the MPV was associated with bone marrow metastasis and increased cell death in advanced-stage cancer (Aksoy et al, 2008;Kumagai et al, 2015). However, there have not been any studies on the relationship between the MPV and NPC.…”
Section: Discussionmentioning
confidence: 96%
“…Even though studies analysing the relationship between MPV and the other types of cancer have been done we still have little information about the relationship between NPC and MPV. Many studies have analysed the relationship between the MPV and cancer (Aksoy et al, 2008;Kumagai et al, 2015;Oncel et al, 2015). One study reported a considerable decrease in the MPV values in some types of cancer (Oncel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Son zamanlarda yapılan çalışmalarda MPV ile değişik kanser tipleri arasındaki ilişkiye de dikkat çekilmiştir, tedavinin baş-langıcında düşük MPV değerinin ilerlemiş küçük hücreli dışı akciğer kanserli hastalarda kötü prognoz prediktörü olabileceği raporlanmıştır (24,25). Bizim çalışmamızda her ne kadar MPV median değeri normal sınırlar arasında kalsa da ACE yükselirken MPV değerinin düşüyor olması düşük MPV değerlerinin hastalığın prognoz tahmininde kullanabileceğini düşündürmektedir.…”
Section: Sonuçunclassified